Pengaturan Hukum dan Pertanggungjawaban Pidana dalam Program Makan Bergizi Gratis (MBG) dalam Kajian Prinsip Pelayanan Publik dan Akuntabilitas Negara - Khairiah, Umi; Saputra, Jarnawi Hadi; Warsiman; Sipahutar, Anjani (Jurnal Ilmiah Penegakan Hukum, 2025)
The Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) is a strategic government policy aimed at improving community nutritional quality, reducing stunting rates, and expanding access to healthy food for vulnerable groups. As a part of public services, the program must be implemented based on the principles of transparency, accountability, and legal certainty as mandated by the 1945 Constitution, the Food Law, Consumer Protection Law, Public Service Law, and State Finance Law. This study employs a normative juridical method using statutory, conceptual, and analytical approaches to examine the legal framework, potential criminal liabilities, and normative proposals to strengthen the accountability of the MBG program. The findings indicate that, although the MBG program has a strong normative legal foundation, the absence of comprehensive technical regulations still poses risks of overlapping authorities, inconsistent standards, and weak oversight. Furthermore, deviations in program implementation may lead to criminal liabilities, particularly regarding violations of food safety, consumer rights, corruption in procurement processes, abuse of authority, and breaches of public health standards. Therefore, the formulation of specific regulations, enhanced budget transparency, strengthened minimum service standards, and optimized supervisory mechanisms are essential to ensure that the MBG program is implemented safely, effectively, and accountably.